2016
DOI: 10.1245/s10434-016-5673-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Local Recurrence After Simple and Skin-Sparing Mastectomy Performed in Patients with Ductal Carcinoma In Situ

Abstract: BackgroundThe incidence of ductal carcinoma in situ (DCIS) is increasing with the use of screening mammography, and approximately 30% of all women diagnosed with DCIS are treated by mastectomy. There is increasing use of a skin-sparing mastectomy (SSM) approach to surgically excise DCIS as this facilitates immediate breast reconstruction. The rates of locoregional recurrence (LRR) after simple mastectomy performed for pure DCIS are historically reported as 1%; however, international data suggest that LRR after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…However, compared to standard mastectomy, IBR with preservation of the entire skin envelope has raised concerns about the oncological safety of SSM in terms of local recurrence . The local recurrence rate (skin and lymph node) after SSM was reported to be between 3.3% and 7.0% in previous papers and we frequently experienced similar outcomes . From an oncological point of view, it is necessary for SSM to be performed safely.…”
Section: Introductionmentioning
confidence: 77%
“…However, compared to standard mastectomy, IBR with preservation of the entire skin envelope has raised concerns about the oncological safety of SSM in terms of local recurrence . The local recurrence rate (skin and lymph node) after SSM was reported to be between 3.3% and 7.0% in previous papers and we frequently experienced similar outcomes . From an oncological point of view, it is necessary for SSM to be performed safely.…”
Section: Introductionmentioning
confidence: 77%
“…Many series do not report on margin involvement. Reported margin involvement rates in both Europe and USA after mastectomy are low (1-7%) compared to reported UK rates of up to 29% [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 95%
“…A UK study of patients with DCIS found a LRR of 5.9% in patients undergoing mastectomy and reconstruction with margin involvement a major predictor for LRR. [5] Most of the literature assessing the oncological safety of mastectomy and immediate breast reconstruction comes from single centres with an institutional policy on management of margins. Many series do not report on margin involvement.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that 0 of 44 patients with ductal carcinoma in situ (DCIS) relapsed upon SSM, while 10 out of 177 with invasive ductal carcinoma presented relapse within 10 years [ 14 ]. When it does occur, DCIS relapse with SSM has been correlated with the young age of the mastectomy patients [ 15 ].…”
Section: Understanding the Zone To Be Reconstructedmentioning
confidence: 99%